The Influence of Regulatory Compliance and Technology Adaptability on The Effectiveness of Goods and Services Procurement for Korsabhara Procurement Actors Indonesian National Police Security Agency - Rizki Abdillah; Harries Madiistriyatno; Nurwulan Kusumadewi (Dinasti International Journal of Management Science, 2026)
The purpose of this study is to determine the effect of regulatory compliance on the effectiveness of procurement of goods and services, the effect of technological adaptability on the effectiveness of procurement of goods and services and to determine the effect of regulatory compliance and technological adaptability on the effectiveness of procurement of goods and services on procurement actors Korsabhara Baharkam Polri. This is proven by the results of the partial test (t test) which shows a calculated t value of 3.588 greater than the t table of 1.991 with a significance level of 0.000 <0.05, Technology Adaptability has a positive and significant effect on the Effectiveness of Procurement of Goods and Services. The results of the partial test show a calculated t value of 7.256 greater than the t table of 1.991 with a significance level of 0.000 <0.05. Compliance with Regulations and Technology Adaptability simultaneously have a positive and significant effect on the Effectiveness of Procurement of Goods and Services. The results of the simultaneous test (F test) F count value of 64.471 is greater than the F table of 2.73 with a significance of 0.000 <0.05, indicating that the two independent variables have a significant influence on the effectiveness of procurement of goods and services. The coefficient of determination (R Square) value of 0.651 means that 65.1% of the variation in the effectiveness of procurement of goods and services can be explained by these two variables, 34.9% is influenced by other factors not examined in the study.